Mid-Nineteenth-Century Population Movement in the Anglo-Scottish Border Region. (3rd July 2022) - Barke, Michael; King, Helen; Welsh, David
ABSTRACT: Using data from six sample parishes, this article examines the migration of predominantly agricultural labour across the Anglo-Scottish border in the mid-nineteenth century. The main purpose is to establish the extent to which the Border formed a barrier to movement at this time. A largely similar agricultural system within the Border region, with a specific character to its employment processes, appears to have been significant in reducing any negative impact upon the movement of labour. Furthermore, an examination of features such as religion, co-habitation and marriage patterns, suggests that for many Border residents, being born in the neighbouring country but living in the other one does not appear to have constituted any significant deterrent to social interaction.